Small GTP-binding protein PdRanBP regulates vascular tissue development in poplar. Issue 1 (December 2016) - Li, Shaofeng; Huang, Qinjun; Zhang, Bingyu; Zhang, Jianhui; Liu, Xue; Lu, Mengzhu; Hu, Zanmin; Ding, Changjun; Su, Xiaohua
Abstract Background Previous research has demonstrated that ectopic expression of Ran-binding protein (RanBP) inArabidopsis results in more axillary buds and reduced apical dominance compared to WT plants. However, the function ofRanBP in poplar, which has very typical secondary growth, remains unclear. Here, thePopulus deltoides (Marsh.)RanBP gene (PdRanBP ) was isolated and functionally characterized by ectopic expression in a hybrid poplar (P. davidiana Dode × P. bolleana Lauche). Results PdRanBP was predominantly expressed in leaf buds and tissues undergoing secondary wall expansion, including immature xylem and immature phloem in the stem. Overexpression ofPdRanBP in poplar increased the number of sylleptic branches and the proportion of cells in the G2 phase of the cell cycle, retarded plant growth, consistently decreased the size of the secondary xylem and secondary phloem zones, and reduced the expression levels of cell wall biosynthesis genes. The downregulation ofPdRanBP facilitated secondary wall expansion and increased stem height, the sizes of the xylem and phloem zones, and the expression levels of cell wall biosynthesis genes. Conclusions These results suggest thatPdRanBP influences the apical and radial growth of poplar trees and thatPdRanBP may regulate cell division during cell cycle progression. Taken together, our results demonstrated that PdRanBP is a nuclear, vascular tissue development-associated protein inP. deltoides .